TIMING OF EARLY PROTEROZOIC MAGMATISM ALONG THE SOUTHERN MARGIN OF THE SIBERIAN CRATON (KITOY AREA) - Poller U.; Todt W.; Gladkochub D.P.; Donskaya T.V.; Mazukabzov A.M.; Sklyarov E.V. (My University, 2004)
Several granites and basement gneisses along the southern margin of the Siberian Craton were sampled to obtain precise age constrains and compositional isotopic data. The analysed granite plutons are interpreted to have been emplaced between 1880 and 1850 Ma, and are related to Palaeoproterozoic collisional and post-collisional events. Pb-Pb whole data of a granulite (1884 ± 26 Ma) and a two mica granite (1821 ± 29 Ma) constrain these U-Pb single zircon ages. Sr, Nd and Pb-Pb isotope data reveal the crustal origin of the investigated rocks and the reworking of Archaean material. Nevertheless, a minor influence of a mantle component is still visible in the Pb isotopes. Geodynamically, the magmatic and metamorphic ages in the Kitoy area are linked to several Early Proterozoic events along the southern margin of the Siberian Craton. Since these events are all older than the assembly of Rodinia (about 1·4 Ga ago) the collisional processes are linked to the consolidation of the Siberian Craton itself in Early Proterozoic times.
Keywords: Proterozoic; Precambrian::Proterozoic; Докембрий::Протерозой